Assessing thermal and economic performance of solar dryers in sustainable strategies for bottle gourd and tomato preservation - Suraparaju, Subbarama Kousik; Elangovan, Elavarasan; Muthuvairavan, Guna; Samykano, Mahendran; Elumalai, P. V.; Natarajan, Sendhil Kumar; Rajamony, Reji Kumar; Balasubramanian, Dhinesh; Fouad, Yasser; Soudagar, Manzoore Elahi M.; Miao, Zhang; Sivalingam, Krishna Moorthy (Nature Research, 2024)
The traditional approach of open-sun drying is facing contemporary challenges arising from the widespread adoption of energy-intensive methods and the quality of drying. In response, solar dryers have emerged as a sustainable alternative, utilizing solar thermal energy to effectively dehydrate vegetables. This study investigates the performance of a single-basin, double-slope solar dryer utilizing natural convection for drying bottle gourds and tomatoes, presenting a sustainable alternative to traditional open-sun drying. The solar dryer exhibited superior moisture removal efficiency, achieving a 94.42% reduction in tomatoes and 83.87% in bottle gourds, compared to open-sun drying. Drying rates were significantly enhanced, with maximum air and plate temperatures reaching 54.42 °C and 63.38 °C, respectively, accelerating the dehydration process. Moisture diffusivity analysis revealed a marked improvement in drying behavior under solar drying, with values ranging from 3.12 × 10−11 to 4.31 × 10−11 m2/s for bottle gourds, and 4.65 × 10−11 to 2.31 × 10−11 m2/s for tomatoes. Energy efficiency assessments highlighted the solar dryer’s advantage, with exergy efficiency peaking at 61.78% for bottle gourds and 68.5% for tomatoes. Furthermore, the activation energy required for drying was significantly lower in the solar dryer (29.14–46.41 kJ/mol for bottle gourds and 27.16–55.42 kJ/mol for tomatoes) compared to open-sun drying, enhancing energy conservation. Visual inspections confirmed the superior quality of the solar-dried vegetables, free from dust and impurities. An economic analysis underscored the system’s viability, with payback periods of 2 years for bottle gourds and 1.6 years for tomatoes. Overall, this study demonstrates the efficacy of solar dryers in optimizing vegetable preservation while promoting energy efficiency, aligning with global sustainability goals by reducing post-harvest losses and supporting eco-friendly practices.